Actores «Invisíveis» do Desenvolvimento em África: o kindoki na racionalização de comportamentos no meio rural de Cabinda (Angola) - João Milando (Cadernos de Estudos Africanos)
Institutionalized development has been a failure in Africa. The causes of this failure are manifold and can be found as much as within the development complex as inside the target populations of the externally induced interventions. The development adversities within the target groups of the projects have been subject to a great number of studies. However, these studies have not succeeded in explaining adequately the characteristics of the local organizational landscapes. The text deals with predominant social dynamics in the rural areas of Cabinda (Angola) that act as rationalization instances of the behaviors of diverse social actors. However these dynamics have been ignored in locally implemented development projects. They are social dynamics that comprise (and express) the tension between «tradition» and «modernity», providing analytical inputs for a better understanding of the complexity of externally induced social change in these societies.